Mesenchymal stromal/stem cell-derived exosomes and genitourinary cancers: A mini review - Salehpour, Aria; Balmagambetova, Saule; Mussin, Nadiar; Kaliyev, Asset; Rahmanifar, Farhad (Frontiers in Cell and Developmental Biology, 2023)
Mesenchymal stromal/stem cell- (MSC-) derived exosomes are gaining popularity for their involvement in tissue repair and repressing various tumors through extensive patterns. Nevertheless, the impact of extracellular vesicles produced by stem cells on tumor formation and progression is controversial and seems to depend on several factors. The utilization of MSCs’ various capabilities in urogenital neoplasms is widely regarded as a potential future therapeutic as well. These genitourinary neoplasms include prostatic neoplasms, ovarian neoplasms, cervical neoplasms, endometrial neoplasms, bladder neoplasms, and renal cell neoplasms. The present study has concentrated on the most recent information on genitourinary neoplasms employing MSCs derived exosomes’ many capabilities, such as delivering effective RNAs, extensive tissue compatibility, and specificity with tumor identification without inherent limitations of cell therapy.